The Associations between the Number of School Sports Teams That a Student Regularly Participates in and Factors Such as Perceived Stress, Loneliness, and Sleep Satisfaction among Korean Adolescents Who Have Attempted Suicide - Jeonga Kwon; Jusun Jang (MDPI AG, 2024)
Adolescents who have attempted suicide are more likely to experience a recurrence of suicidal behavior, thus necessitating systematic follow-ups and management. We aimed to investigate the association between the number of school sports teams that a student regularly participates in and psychological factors such as perceived stress, loneliness, and sleep satisfaction among 1393 Korean adolescents who have attempted suicide by using data from the 2022 Korea Youth Risk Behavior Survey. Frequency analyses were performed to evaluate participant characteristics. Chi-square analyses were used to examine the differences in participant characteristics according to the number of teams. Multivariate logistic regression analysis was used to examine the associations between the number of teams and perceived stress, loneliness, and sleep satisfaction. Our results indicated that participating in a greater number of sports teams at school was more strongly associated with reduced perceived stress, reduced loneliness, and increased sleep satisfaction. Specifically, the odds ratio (OR) for feeling very much stressed was 0.613 (range: 0.387-0.969; p = 0.036) among the participants who belonged to one team. Among those who belonged to two teams, the OR for feeling very much stressed was 0.482 (range: 0.281-0.286; p = 0.008). Among those who belonged to two teams, the OR for feeling a lot of stress was 0.514 (range: 0.304-0.870; p = 0.013), and that for not feeling much stress was 2.663 (range: 1.103-6.426; p = 0.029). The OR for not feeling much stress was 4.697 for those who belonged to three teams (range: 1.531-14.408; p = 0.007) and 6.671 for those who belonged to four or more teams (range: 1.858-23.953; p = 0.004). The OR for feeling no stress at all was 11.629 (range: 2.229-60.661; p = 0.004) for those who belonged to three teams and 93.531 (range: 19.260-454.207; p < 0.001) for those who belonged to four or more teams. In terms of loneliness, the OR for rarely feeling lonely was 2.651 (range: 1.148-6.123; p = 0.022) among those who belonged to one team. The OR for feeling lonely all the time was 0.370 (range: 0.155-0.884; p = 0.025) among those who belonged to two teams. In terms of sleep satisfaction, the OR for having very sufficient sleep was 4.371 (range: 1.627-11.742; p = 0.003) for those who belonged to four or more teams. These results suggest that school sports are an advantageous tool for suicide prevention, given their low costs, absence of side effects, and ease of participation.